2011
DOI: 10.1074/jbc.m111.237966
|View full text |Cite
|
Sign up to set email alerts
|

Protein-disulfide Isomerase Displaces the Cholera Toxin A1 Subunit from the Holotoxin without Unfolding the A1 Subunit

Abstract: Protein-disulfide isomerase (PDI) has been proposed to exhibit an "unfoldase" activity against the catalytic A1 subunit of cholera toxin (CT). Unfolding of the CTA1 subunit is thought to displace it from the CT holotoxin and to prepare it for translocation to the cytosol. To date, the unfoldase activity of PDI has not been demonstrated for any substrate other than CTA1. An alternative explanation for the putative unfoldase activity of PDI has been suggested by recent structural studies demonstrating that CTA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
127
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(148 citation statements)
references
References 56 publications
(58 reference statements)
20
127
0
1
Order By: Relevance
“…From these results we concluded that CTA1 has partially disordered secondary structure and can be placed in the intrinsically disordered (ID) protein class. The behavior of cholera toxin A1 polypeptide of regular units of helices and β-sheets interrupted by coils were in close agreement to the work of Ampapathi et al [16] who observed the secondary structure through circular dichroism spectroscopy and 2D nuclear magnetic resonance spectroscopy and that of others [13][14][15][16].…”
Section: Secondary Structure Analysissupporting
confidence: 87%
See 3 more Smart Citations
“…From these results we concluded that CTA1 has partially disordered secondary structure and can be placed in the intrinsically disordered (ID) protein class. The behavior of cholera toxin A1 polypeptide of regular units of helices and β-sheets interrupted by coils were in close agreement to the work of Ampapathi et al [16] who observed the secondary structure through circular dichroism spectroscopy and 2D nuclear magnetic resonance spectroscopy and that of others [13][14][15][16].…”
Section: Secondary Structure Analysissupporting
confidence: 87%
“…The first 132 amino acids formed a compact globular unit composed of a mixture of α-helices and β-strands [10,12,13]. The catalysis is thought to occur in well define fissure on the free surface of A-subunit [10,12,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disulfide bond linking CTA1 to CTA2 must then be reduced (4), which only occurs after the CT holotoxin moves from the cell surface to the endoplasmic reticulum (ER) through a series of vesicle-mediated trafficking steps collectively termed retrograde transport (5,6). Reduction of the CTA1/CTA2 disulfide bond permits the chaperone-assisted dissociation of CTA1 from CTA2/CTB 5 (7,8). CTA1 is held in a stable conformation by its interactions with the holotoxin (9,10), but the isolated CTA1 polypeptide is an unstable protein that will spontaneously unfold at 37°C upon its separation from CTA2/CTB 5 (11).…”
Section: Cholera Toxin (Ct)mentioning
confidence: 99%